Preventing and management of mouth ulcers caused by orthodontic - Hashim Farran, Waleed; Alshudukhi, Alhanouf Abdullah; Namazi, Mohammed Ahmed; Aljakthami, Wafa Nawaf; Alotaibi, Nada Fahad; Alsultan, Nouf Abdullah; Hudithi, Hassan Ibrahim Al; Alshehri, Faisal Ali; Alamer, Amwaj Yahya; Alessa, Nujud Muzhir; Alsawat, Lujain Salem (International Journal Of Community Medicine And Public Health, 2025)
Orthodontic-induced mouth ulcers are a common complication arising from mechanical irritation and increased plaque accumulation during treatment. These painful lesions significantly impact the comfort and compliance of patients undergoing orthodontic care. Various factors contribute to their development, including appliance design, oral hygiene, dietary habits, stress, and systemic conditions like nutritional deficiencies. Effective prevention and management strategies are essential to mitigate these effects and enhance patient outcomes. Prevention focuses on minimizing mechanical trauma through improved appliance designs such as rounded brackets and self-ligating systems, and the use of protective barriers like orthodontic wax and silicone strips. Maintaining optimal oral hygiene with adjunctive tools, antimicrobial rinses, and dietary adjustments plays a pivotal role in reducing plaque accumulation and preventing mucosal injuries. Behavioral interventions, including stress management and addressing parafunctional habits, further support ulcer prevention. Management approaches include the use of topical treatments like corticosteroid-based ointments and bio-adhesive gels to alleviate pain and promote healing. Low-level laser therapy (LLLT) accelerates tissue repair and provides analgesic effects, emerging as an effective adjunctive treatment. In more severe cases, systemic antibiotics or anti-inflammatory medications may be employed to control secondary infections and support immune responses. Patient education is critical in ensuring adherence to these strategies, emphasizing the importance of dietary modifications, stress control, and consistent oral care. Comprehensive care combining innovative technologies, evidence-based treatments, and personalized patient support addresses both the etiology and impact of orthodontic-induced ulcers. These integrated strategies not only reduce the incidence and severity of lesions but also improve overall patient satisfaction and treatment compliance. As advancements in materials and therapeutic modalities continue, the potential for enhanced outcomes in orthodontic care grows, ensuring better quality of life for patients during treatment.